Pathways of a Cell Biologist Through Yet Another Eye - Inoué, Shinya (Springer Biographies, 2016)
This book is the autobiography of Shinya Inoué, tracing his life from childhood to the present. Though he has made many contributions to science, perhaps the most remarkable one involves the visualization of dynamics in living cells by means of a polarizing light microscope, an innovation that changed the face of cell biology. Addressing readers curious to know why and how he achieved such success, the story begins with a prologue describing the end of World War II and Inoué's lifelong collaborator, the great cell biologist Katsuma Dan. Following the prologue, the author's childhood and teenage experiences during World War II are described, before the focus shifts to his scientific career and personal life. The book not only offers important tips for young researchers, it will also help them develop a passion for science.